Acceptability and Nutritional Composition of Dragon Fruit–Moringa–Roselle Velva as a Functional Snack for Stunted Children - Ajeng Kinanti Anggraini; Juliana Christyaningsih; Melina Sari (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Introduction Stunting is a chronic form of undernutrition that occurs during the growth and development of children.Purpose This study aims to identify acceptability and analyze protein and fiber content in Velva Dragon Fruit Moringa with Roselle Addition as an alternative snack for stunting children. Methods This study used a post-test only control group design to evaluate the effect of the addition of rosela on the protein and fiber content of dragon-moringa fruit velva. Three formulations were tested with different levels of rosela (23.3 g; 21.67 g; 20 g). The hedonic test was conducted by 25 trained panelists and used informed consent, analyzed using the Kruskal-Wallis and Mann-Whitney tests with significantly different results (p < 0.05). Protein levels were analyzed by the Kjeldahl method and fibers by gravimetric method. Results The KR03 formulation showed the highest sensory acceptance with a mean score of 3.85. Nutritional analysis showed that KR03 contained 6.89% protein and 0.51% fiber. ConclusionThe KR03 formulation of velva dragon fruit-moringa with roselle addition demonstrated the highest acceptability among panelists, indicating its potential as a preferred alternative snack for children at risk of stunting. Its balance between taste and nutritional value supports its feasibility as a functional food intervention.